Cell-Based Assays in High-Throughput Screening for Drug Discovery - Zang, Ru; Li, Ding; Tang, I-Ching; Wang, Jufang; Yang, Shang-Tian (International Journal of Biotechnology for Wellness Industries, 2012)
Drug screening is a long and costly process confronted with low productivity and challenges in using animals, which limit the discovery of new drugs. To improve drug screening efficacy and minimize animal testing, recent efforts have been dedicated to developing cell-based high throughput screening (HTS) platforms that can provide more relevant in vivo biological information than biochemical assays and thus reduce the number of animal tests and accelerate the drug discovery process. Today, cell-based assays are used in more than half of all high-throughput drug screenings for target validation and ADMET (absorption, distribution, metabolism, elimination and toxicity) in the early stage of drug discovery. In this review, we discuss the uses of different types of cells and cell culture systems, including 2D, 3D and perfusion cell cultures, in cell-based HTS for drug discovery. Optical and electrochemical methods for online, non-invasive detection and quantification of cells or cellular activities are discussed. Recent progresses and applications of 3D cultures and microfluidic systems for cell-based HTS are also discussed, followed with several successful examples of using cell-based HTS in commercial development of new drugs. Finally, a brief discussion on potential applications of cell-based HTS for screening phytochemicals and herbal medicines is provided in this review.